What predicts the number of attempts to pass the driving test? A case from Norwegian driving education model. (October 2021) - Simsekoglu, Özlem; Suzen, Elisabeth
Abstract: This study focuses on examining the relationships between the variables within the driving education process in Norway by aiming to answer three research questions: 1) Is there a difference between learner drivers above and below 25 years old in time spent at different steps and between theory and practical tests? 2) Do the time spent during different steps of the driving education, the number of attempts in the theory and practical tests differ by demographic variables? 3) What variables predict the number of attempts to pass the practical test? Data were extracted from two registry systems provided by the Norwegian Public Roads Administration. It included information from a randomized sample of 452 learner drivers who took their driving license in 2017. The age mean of the learner drivers when they got their license was 24.3 and most of them (54.6%) were males. Independent samples t -test results showed that compared to the learner drivers below 25 years, those above 25 years old spent significantly more time during steps 3 and 4, and had significantly more attempts to pass both theory and practical tests. In terms of the demographic variables, age was significantly and positively correlated with the time spent during the whole driving education and the number of attempts both in the theory and practical tests indicating that time spent for driving education and the number of attempts in the tests tend to increase with the increasing age. Also, the average time spent between taking the theory test and completing step 4 was significantly more among males than females. Test location had no significant influence on the number of attempts to pass the practical test. Finally, two separate regression analyses were conducted to examine the predictors of the number of attempts to pass the practical test for learner drivers both below and above 25 years old. For both groups, the strongest predictor of the number of attempts in the practical test was time spent between the theory test and the practical test, which indicates that as the time gap between the two tests increases learner drivers are more likely to fail at the practical test. Results are discussed for their implications which could be useful to improve the driving education process both in Norway and in other countries with similar driving education models. Highlights: Relationships between training time, age, gender, test location, and outcome of the driving tests were examined The sample included 452 learner drivers who took their driving license in 2017 in Norway Time spent on the driving education and number of attempts in the tests increased with the increasing age Test location had no significant influence on the number of attempts to pass the driving test As time gap between theory and driving test increased learner drivers were more likely to fail at the driving test